PRINCIPLES OF STATE-BUILDING: THE CASE OF KOSOVO - Bekim Podrimqaku; Kujtim Bytyqi (European Scientific Journal, ESJ, 2014)
This study intends to analyze and discuss the principles on the bases of which Kosovo declared its independence on 17 February 2008. Kosovo was a particular case in terms of this principles and the claims between Albanian and Serbian over its territory. The paper puts emphasis on, the anti-constitutional removal of Kosovo's autonomy in 1989, the repression exercised over the civilian population in Kosovo as well as the arguments for the right to selfdetermination of Kosovo as the last breakaway territory after the disintegration of Yugoslavia. In addition, arguments takes into account the ethnic principle and the principle of Uti Possidetis based on which all other Republics of former Yugoslavia (except Kosovo) gained their independence through Badinter Commission. Furthermore, paper analyzes the relevance of these principles in the case of Kosovo, and how they were used by other countries in their statehood stories. Finally, the paper relies on the opinion given by the International Court of Justice over Kosovo declaration of independence by the leaders of Kosovo institutuions.